PENGGUNAAN RADIOGRAF GIGI UNTUK KEPENTINGAN IDENTIFIKASI FORENSIK - Sita Rose Nandiasa; Bramma Kiswanjaya; Mindya Yuniastuti (Odonto : Dental Journal, 2016)
Background: Tooth has a unique characteristic. Teeth often used for forensic identification especially when the other parts of the body could not gave a difference feature used for identification.Discussion: Tooth is part of the body known for its resistant against external influence making it as an important primary identifier. Dental radiographic can act as a helpful tool in identification process to compare antemortem and postmortem data. Radiograph can give a detail features from the teeth and their surroundings, especially digital radiograph so it can ease the identification process.Conclusion : forensic identification using radiograph can be trusted.